Antimicrobial effects of multifunctional ingredients with potential application for ready to eat meat and poultry products - Lanzrath, Russell (Kansas State University, 2016)
Consumer demand for clean-label and 'all natural' food products has created the need to investigate antimicrobials derived from natural sources. Multifunctional ingredients are food additives that have multiple properties to reduce fat, limit salt, retard oxidation, increase water-holding capacity and inhibit bacterial growth in foods. Multifunctional ingredients that exhibit antimicrobial effects in meat and poultry products can facilitate consumers demand for clean and 'all natural' labels while reducing foodborne illness risk. Previous scientific research has shown that plant essential oils are known to contain active components to prevent oxidation in meat products, but emerging data have shown that these plant-based ingredients also contain antimicrobial properties. Plant essential oils such as basil oil has shown limited Salmonella Enteritidis inhibition in meat model systems and thyme oil has shown Listeria monocytogenes inhibition in low fat beef hotdogs. Intrinsic and extrinsic parameters of meat systems can alter the antimicrobial efficacy of plant essential oils. Although antimicrobial effects were observed with plant essential oils, effective usage levels may be limited to sensory characteristics in certain meat and poultry products. Natural extracts have shown potential antimicrobial properties in meat and poultry applications. Rosemary extract has been shown to suppress the growth of Enterobacteriaceae, Pseudomonas, and yeast and molds in fresh sausage. Grapefruit seed extract has shown inhibition against Campylobacter jejuni in poultry skin and meat models and E. coli O157:H7 in moisture enhanced beef homogenate models. The addition green tea extract in ground beef has been shown to reduce D-values while cooking and inhibit outgrowth of C. perfringens spores during extended chilling of cooked ground beef. Grape seed extract has been shown to reduce Listeria monocytogenes, E. coli O157:H7 and Salmonella Typhimurium populations in cooked lean ground beef stored for 9 days at 4°C. Scientific research findings for plant essential oils and extracts confirm that multifunctional ingredients are relevant to meat and poultry products as potential food additives to control undesirable pathogen and spoilage bacteria while meeting consumer demand for natural, clean-label ingredients.
Keywords: Ready to eat; Meat; Antimicrobial; Multifunction ingredients; Natural extracts; Plant esstential oils